C-Reactive Protein (CRP) levels in neonatal meningitis in England: an analysis of national variations in CRP cut-offs for lumbar puncture - Jonathan P. Sturgeon; Beatrice Zanetti; Dwight Lindo (BMC, 2018)
Abstract Background Recent National Institute for Health and Care Excellence (NICE) CG149 guidelines suggest considering performing a lumbar puncture (LP) to investigate for meningitis in early-onset sepsis in a neonate when a C-reactive protein (CRP) level >10mg/L, but the evidence for this recommendation is poorly defined. Methods Data on trust-wide LP protocols, neonatal meningitis incidence, lumbar punctures, and CRP levels seen in cases of neonatal meningitis were asked of all 137 trusts in England that recorded a birth in 2017. Our local Kingston Hospital data on every LP performed was obtained to estimate the specificity of CRP rises. Results 73/123 (59.3%) of trusts follow the NICE CG149 recommendation of considering an LP if the CRP >10mg/L. The national incidence of neonatal meningitis was 0.467/1,000 births, and an LP was performed in 1.37% of all babies, which was significantly higher in trusts considering the CRP > 10mg/L cut-off. A CRP > 10mg/L cut-off sensitivity was 88.9% based on the highest CRP level 4 days around the LP from national data of 199 cases; specificity was 78.8% based on our single-unit analysis. Conclusions Proposing a universal CRP > 10mg/L cut-off for a lumbar puncture has been counter-productive in England. Following it generates significantly more LPs, to the point that 40.7% of trusts have chosen not to follow it. It also has poor sensitivity missing over 11% of meningitis. We therefore do not recommend a universal cut-off, rather considering the whole clinical picture (including prematurity) when considering whether to do an LP.